Zad:3/154 p. Niech A oznacza sumę algebraiczną 3x-y, niech B oznacza x-1,a C niech oznacza sumę -3x-y.Wykonaj działania: a) A+B b) A+B-C c) A-B-C d) A-(B-C)
crazyalusiaxd
A) 3x - y * x-1 = 2x - y b) 3x - y * x-1 - (-3x-y) = 3x - y * x-1 + 3x - y = 5x - 2y c) 3x - y - x-1 - (-3x-y) = 3x - y - x-1 + 3x-y = 5x - 2y d) 3x-y - ( x-1- [-3x-y]) = 3x-y -(x-1 + 3x - y) = 5x - 2y
b) 3x - y * x-1 - (-3x-y) = 3x - y * x-1 + 3x - y = 5x - 2y
c) 3x - y - x-1 - (-3x-y) = 3x - y - x-1 + 3x-y = 5x - 2y
d) 3x-y - ( x-1- [-3x-y]) = 3x-y -(x-1 + 3x - y) = 5x - 2y